Interleukin 1 Beta Gene Polymorphism in Schizophrenia and Psychotic Depression - Rady, Ahmed; Elsheshai, Adel; Abdallah, Ibtisam; Elkholy, Osama; Wafa, Heba Abou el (Gene expression to genetical genomics, 2010)
Ahmed Rady1, Adel Elsheshai1, Ibtisam Abdallah2, Osama Elkholy1 and Heba Abou el Wafa11Department of Psychiatry, Alexandria University, Alexandria, Egypt. 2Department of Genetics, Institute of Medical Research, Alexandria, Egypt. AbstractThe proinflammatory interleukin 1 beta serum level is elevated in schizophrenic patients. Like other proinflammatory cytokine, it is in part dependant on genetic expression, so it may represent a candidate susceptibility gene for schizophrenia. It plays a crucial role in development of the Central Nervous System (CNS) and may, hence, influence brain morphology in schizophrenia. The theory that psychotic depression is a distinct syndrome that has to be differentiated from non psychotic depression, is supported by literature showing substantial difference between them in clinical manifestations, biological laboratory measures, family transmission, course, response to treatment and prognosis. Our work attempts to assess Interleukin 1 beta gene polymorphism in psychotic depression and schizophrenia, which may potentially represent a genetic differentiating biological marker, taking in consideration the diagnostic difficulty that rises when evaluating those two disorders, though of different management and outcome, but largely similar in terms of presenting symptoms.